2017
DOI: 10.1007/s00408-017-0052-z
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Depression, and Health-Related QOL in Patients Diagnosed with PAH or CTEPH

Abstract: While both cohorts of patients suffer from a reduced HRQOL as well as depression and anxiety, decreases in mental health parameters are more pronounced in the CTEPH cohort. This suggests a strong effort to improve early detection, especially in dyspneic patients with classical risk factors for CTEPH and PAH and argues for mental illness interventions alongside routine clinical care provided to patients diagnosed with PAH or CTEPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 61 publications
1
47
1
Order By: Relevance
“…Pfeuffer et al suggest an important difference in the prevalence of anxiety, depression, and perception of health-related quality of life (HRQoL) between chronic thromboembolic pulmonary hypertension (CTEPH) and PAH patients, with higher scores in CTEPH cohorts. 20 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pfeuffer et al suggest an important difference in the prevalence of anxiety, depression, and perception of health-related quality of life (HRQoL) between chronic thromboembolic pulmonary hypertension (CTEPH) and PAH patients, with higher scores in CTEPH cohorts. 20 …”
Section: Resultsmentioning
confidence: 99%
“…Harzheim et al confirmed a little difference in anxiety and depression prevalence between PAH (22.5%) and CTEPH (25%) patients, but we must outline that the cohorts analyzed by Harzheim were younger than patients studied by Pfeuffer. 17 , 20 …”
Section: Resultsmentioning
confidence: 99%
“… 7 The results of our study reveal that in addition to the multiple impacts mentioned above, patients with PH are also likely to experience psychological states of anxiety, depression, worthlessness, uncertainty about the future, and hopelessness. 5 , 21 , 22 Although past studies have pointed out the importance of psychiatric referrals in patients with PH, 20 , 23 one study has shown that the percentage of patients with PH with psychological and emotional disturbances undergoing psychiatric treatment is low. 24 Our study finds that the underlying cause of the low percentage of psychiatric treatment involved is not that the medical team fails to notice the patients’ psychological and emotional disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…spinal cord injury, interstitial lung disease, or treatment-resistant cancer [16]. An interesting comparison of quality of life (QoL) in PAH and chronic thromboembolic pulmonary hypertension (CTEPH) patients was presented by Pfeuffer et al [17]. CTEPH is a rare, progressive pulmonary vascular disease, that is usually a consequence of prior acute pulmonary embolism [18].…”
Section: Quality Of Lifementioning
confidence: 99%
“…While both cohorts of patients suffered from a reduced HRQoL as well as depression and anxiety, decreases in mental health parameters were more pronounced in the CTEPH cohort. This suggests the need for intensive efforts to improve early detection, especially in dyspnoeic patients with classical risk factors for PAH and CTEPH and mental health interventions alongside routine clinical care provided to patients diagnosed with PAH or CTEPH [17].…”
Section: Quality Of Lifementioning
confidence: 99%